RAPID IMPLEMENTATION OF REAL-TIME REVERSE-TRANSCRIPTION POLYMERASE CHAIN REACTION (REAL-TIME RT-PCR) ASSAY FOR THE DETECTION OF SARS-COV-2 IN A MOROCCAN HOSPITAL - BELEFQUIH, Bouchra; MAHER , Wissal; CHEIKH , Amine; HAMDANI , Wail; ZAID , Younes; KABBAJ , Hakima; SEFFAR , Meryem; DAKKA , Hanae; HADAMI , Khaoula; ALLAOUI, Afaf; BENOUDA , Amina (African Journal of Infectious Diseases (AJID), 2022)
Background: The main challenge faced in the African countries was to implement efficient molecular diagnostic facilities and start Covid-19 diagnosis as fast as possible to handle the rapid and unpredictable rise of cases. Materials, Methods and Results: We describe our experience in implementing a molecular biology unit at Sheikh Zaïd International University Hospital in Rabat, with a delay as short as one week, and starting real-time RT-PCR assay for the detection of SARS-Cov-2 infection, since the outbreak widened in Morocco in mid-March, 2020. Conclusion: The challenges encountered in the first period of Covid-19 pandemic are still present. This work aims to give an example of a rapid and adaptive response in order to maintain our diagnosis ability for Covid-19 and for other pathogens